Germination and viability of eurycoma longifolia jack. seeds after storage under different environments - Nurfaizah, Matra. (Universiti Malaysia Sarawak (UNIMAS), 2006)
A study was conducted to evaluate the effects of storage on gennination and viability of E. longifolia seeds for long tenn conservation. Seeds with 9.76 % of moisture content and 33 % germination were placed in three different environments; ambient room (29°C), refrigerator (4°C) and incubator (36°C) for eight days. Seed stored in refrigerator gave the highest viability with 67 %. Storage in incubator showed gradual decrement of viability throughout the period of storage. Viability and gennination percentages decreased with increased storage period. Regression analysis showed that seeds stored in refrigerator could maintain its viability up to 67 %. Results showed that storage in refrigerator temperature was a suitable condition to store E. longifolia seeds.